2020
DOI: 10.1111/nyas.14556
|View full text |Cite
|
Sign up to set email alerts
|

Guava with an institutional supplementary meal improves iron status of preschoolers: a cluster‐randomized controlled trial

Abstract: The Integrated Child Development Services of India provides Supplementary Nutrition Program (SNP) to preschoolers. Using this platform, the current study examined the impact of diversifying a cereal/pulse-based SNPmeal with guava on iron status and cognitive development among 24-48 months old children. A three-arm, nonblinded, cluster-randomized controlled trial (CTRI/2014/09/004983) included 399 beneficiaries from 28 preschools in 16 villages in Telangana state, India. The villages were randomly assigned to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In summary, 50% of trials were conducted in developed countries [55][56][57][58][59][60] and 50% in low and middleincome countries (LMICs) [61][62][63][64][65][66]. Four experimental studies were conducted in rural areas with low socioeconomic status [61,62,64,66], and six studies in urban areas with high socioeconomic status [55][56][57][58][59][60]. The earliest trial was completed in 2004 [58] and the latest in 2020 [65].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In summary, 50% of trials were conducted in developed countries [55][56][57][58][59][60] and 50% in low and middleincome countries (LMICs) [61][62][63][64][65][66]. Four experimental studies were conducted in rural areas with low socioeconomic status [61,62,64,66], and six studies in urban areas with high socioeconomic status [55][56][57][58][59][60]. The earliest trial was completed in 2004 [58] and the latest in 2020 [65].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Six studies had an overall low risk of bias [55,56,59,60,65,66] and six had a moderate risk of bias [57,58,[61][62][63][64] as indicated in Table 3. Five studies did not record methods of handling withdrawal [57,58,[61][62][63] and two studies [57,64] reported moderate differences between study groups at baseline.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations